SLFN11 Restricts LINE-1 Mobility - Zhongjie Ye; Yuqing Duan; Ao Zhang; Zixiong Zhang; Saisai Guo; Qian Liu; Dongrong Yi; Xinlu Wang; Jianyuan Zhao; Quanjie Li; Ling Ma; Jiwei Ding; et al. (Cells)
Long interspersed element-1 (LINE-1) is the only active autonomous transposon comprising about 17% of human genomes. LINE-1 transposition can cause the mutation and rearrangement of the host’s genomic DNA. The host has, therefore, developed multiple mechanisms to restrict LINE-1 mobility. Here, we report that SLFN11, a member of the Schlafen family, can restrict LINE-1 retrotransposition, and the inhibitory activity requires its helicase domain. Mechanistically, SLFN11 specifically binds to the LINE-1 5′ untranslated region (5′UTR) and blocks RNA polymerase II recruitment, thereby suppressing its transcription. Furthermore, SLFN11 promotes heterochromatinization, suggesting an epigenetic inhibition pathway.